COMPREHENSIVE PUBLIC SMOKING PROGRAM (Tufts Archival Research Center, 2007)
Confidential; Marginalia; Speech on the Comprehensive Public Smoking Program. Includes legislative strategies "repeal, modify or rollback" existing legislation in specific cities and states across the U.S. Includes key allies to oppose smoking restrictions on local and state levels.